PELAKSANAAN PENYIDIKAN TINDAK PIDANA NARKOTIKA YANG DILAKUKAN ANAK POLRES BUKITTINGGI - Yuserlina, Anny (Ensiklopedia Sosial Review, 2020)
The increasing narcotic abuse among this child has filled and added a new pattern of crime. Therefore, when the child becomes a criminal offence the state should provide protection to him. Indonesian law has provided protection to children through various statutory regulations including Law No. 11 of 2012 on the Child criminal justice system. The research method used was Yuridis empirical. The conclusion of the research result is the implementation of an investigation into the child involved in the narcotics transaction in Bukittinggi Police law area conducted by the investigator is basically already in accordance with the criminal (KUHP) and Undang-Undang No. 11 Tahun 2012 Tentang Sistem Peradilan Anak, that apply even in the implementation is not maximally due to limitations. The rights granted to the suspect child are also given the right to be avoided from violence, accompanied by legal counsel and community advisers, the right to issue opinions, views freely, get care and welfare, and the rights are treated equally. Obstacles arising in the investigation of the child involved in the narcotics transaction in the territory of Bukittinggi police, among others, the time for the detention of children is very limited that is 7 days and can be extended 8 days so that investigators must be extra fast to be able to complete the file, must wait for the results of the (BAPAS) research on the child, and the absence of special investigators Efforts to overcome the constraints in the implementation of an investigation into the child involved in narcotic transactions in the region of Bukittinggi police are increasing the ability of investigators in conducting investigations, seeking to have investigators in the police of Bukittinggi can also be appointed as a child investigator, seeking for a special room for the investigation of children so that the child is more freely to make information.